Treatment of infections in cancer patients: an update from the neutropenia, infection and myelosuppression study group of the Multinational Association for Supportive Care in Cancer (MASCC). Issue 3 (4th March 2021) - Rapoport, Bernardo L.; Cooksley, Tim; Johnson, Douglas B.; Anderson, Ronald; Shannon, Vickie R.
ABSTRACT: Introduction: Patients with hematological and advanced solid malignancies have acquired immune dysfunction, often exacerbated by treatment, posing a significant risk for the development of infections. This review evaluates the utility of current clinical and treatment guidelines, in the setting of management of infections in cancer patients. Areas Covered: These include causes of infection in cancer patients, management of patients with high-risk and low-risk febrile neutropenia, management of low-risk patients in an outpatient setting, the role of granulocyte colony-stimulating factor (G-CSF) in the prevention and treatment of neutropenia-related infections, management of lung infections in various clinical settings, and emerging challenges surrounding the risk of infection in cancer patients treated with novel treatments. The literature search was performed by accessing PubMed and other databases, focusing on published clinical trials of relevant anti-cancer agents and diseases, primarily covering the recent past, but also including several key studies published during the last decade and, somewhat earlier in a few cases. Expert Review: Notwithstanding the promise of gene therapy/gene editing in hematological malignancies and some types of solid cancers, innovations introduced in clinical practice include more discerning clinical management such as the generalized use of biosimilar formulations of G-CSF and the implementation of novel, innovative immunotherapies.